The Effect of Chemsketch on STEAM-Based Learning in Improving Critical Thinking Skills on Chemical Bonding Materials - Gusman, Tania Avianda; Vivit Dania; Mutiara Dwi Cahyani (Chemistry Education Department of Education and Teaching Faculty, 2024)
Chemistry learning, especially in Indonesia, has not been able to direct students to master critical thinking skills. Using appropriate media and learning models can improve students' critical thinking skills. One of the efforts to improve critical thinking skills is using Chemsketch media with STEAM-based learning models (Science, Technology, Engineering, Art, Mathematics). This study aims to analyze the effect of using ChemSketch in STEAM-based learning (Science, Technology, Engineering, Art, Mathematics) on improving students' critical thinking skills on chemical bonding material. This study used a Non-equivalent control group design. The population in this study were all grade X students of SMA Negeri 1 Karangwareng in the 2023/2024 school year, with the samples used including one class X-7 as the experimental class and one class X-6 as the control class. The data obtained were then analyzed using the N-Gain and simple linear regression tests. The results showed that: 1) STEAM-based learning significantly increases critical thinking skills with an N-Gain value of 0.66. 2) STEAM-based learning significantly affects critical thinking skills with a value of 0.002. It can be concluded from the results of this study that students in the experimental group experienced a significant increase in critical thinking skills compared to the control group. This indicates that integrating ChemSketch in STEAM-based learning can be an effective strategy to improve students' ability to analyze, evaluate, and solve problems related to chemical bonding.